Seeing the world as creation: Christian sources for an environmentalist age - Longbons, Jarrod (2019)
Twentieth century environmentalist literature tends to blame Christian religious tradition, especially its influence upon Western culture, for introducing ways of “seeing” (theoria) the world of nature (non-human creation) that produce anti-environmental practices. But does Christianity – in its biblical, and ancient/early medieval sources that explain the notions of creation, human uniqueness, and purpose – really promote a vision of nature-culture dualism, despotic anthropocentricism, and thus natural disenchantment? By analyzing the hexameronic material of church fathers, both East and West, we discover that Genesis must not be read in the anti-natural way that modern environmental critics have argued, but as a proto-environmentalist text which, properly interpreted, underwrites responses to modern environmental needs. Maximus the Confessor joins the conversation with dogmatic assistance about environmentalism via the doctrine of creation. Maximus’ work carries the ancient vision of creation into the medieval period, entirely supportive of environmentalist concerns; indeed, his Christological interpretation of creation is perhaps the “greenest” theology of all, for its evaluation of creation’s source and end is wrapped up in divine destiny. Also, Maximus’ Eucharistic theology expresses the idea that the church is ultimately the “community of creation,” implying a dual task of “seeing” creation sacramentally and an ethos for earth care. When Maximus’ creation dogma is synthesized with the “leisure” practice of Josef Pieper, we find a helpful tool for Christian environmental care that affirms the goodness of the world’s being. In conclusion, both the theological foundation in the church fathers and the praxis of Pieper combine to reveal that the broad tradition of Christianity and its mode of “seeing” the world are environmentally sound.